Association between blood viscosity and early neurological deterioration in lacunar infarction - Lee, Hyungwoo; Heo, JoonNyung; Lee, Il Hyung; Kim, Young Dae; Nam, Hyo Suk (Frontiers in Neurology, 2022)
Background: Understanding the factors related to early neurologic deterioration (END) is crucial in the management of patients with lacunar infarction. Blood viscosity is a significant factor for microvascular perfusion. We investigated the association between blood viscosity and occurrence of END in lacunar infarction. Methods: We included consecutive patients admitted for lacunar infarction within 72 hours from symptoms onset. END was defined as an increase in the National Institute of Health Stroke Scale (NIHSS) score ≥2 within 24 hours of admission. Viscosity was measured within 24 hours of hospitalization with a scanning capillary tube viscometer. Viscosity measured at a shear rate of 300 s−1 was defined as systolic blood viscosity (SBV), whereas that measured at a shear rate of 5 s−1 as diastolic blood viscosity (DBV). Results: Of the 178 patients included (median age, 65.5; interquartile range [IQR], 56.0, 76.0], END occurred in 33 (18.5%). DBV was significantly higher in patients with END than those without END (13.3 mPa⋅s [IQR 11.8, 16.0] vs. 12.3 mPa⋅s [IQR11.0, 13.5]; P = 0.023). In the multivariate analysis, DBV was independently associated with the occurrence of END (odds ratio 1.17; 95% confidence interval 1.01–1.36; P = 0.043). Subgroup analysis showed no heterogeneity in the effect of viscosity on the occurrence of END. Conclusions: Blood viscosity at a low shear rate (DBV) was associated with the occurrence of END in patients with lacunar infarction. Blood rheology may be important in pathophysiology of END in patients with lacunar infarction.